The association between vitamin D, vitamin D Binding proteins and VDR polymorphisms in diabetic and non-diabetic patients - Maepa, Setjie Welcome (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.